657 Patient Perspectives on Telesleep Care in COVID Times: An Urban Teaching Hospital Survey. (3rd May 2021) - Munoz, Tomas; Patel, Palakkumar; Viswanath, Shilpa; Prasad, Bharati
Abstract: Introduction: Telehealth is a relatively new tool for patient care, and to reach underserved areas where certain specialties are available. With the advent of the COVID19 pandemic, Telehealth has become a universal way to provide safe and quality patient care. However, Telehealth is a new experience for many providers and patients. We surveyed patients who received telehealth visits in sleep medicine between March and June 2020 to determine patient satisfaction and common technology-related barriers. The goal was to formulate actionable steps for improving patient's experiences and determine the feasibility of long-term telehealth services for sleep medicine. Methods: We interviewed 63 patients by phone, utilizing IRB approved surveys for telehealth satisfaction and technology. Responses were de-identified, tabulated, and analyzed in aggregate using Excel®. Results: 85% of respondents had a high-school diploma or a higher level of education (9.6% students, 39.7% employed, 15.9% unemployed, and 19% retirees). 62% of participants participated in Telehealth for the first time. 89% preferred Telehealth, and 76% rated telehealth experience as good or better than in-person visits. 92% did not require technical assistance during the visit. Long-term telehealth care was acceptable to 63% of participants. Approximately 33% had technology-related barriers (no computer or webcam), and 12% did not have email. However, 89% had smartphones (70% connected to personal internet). Other barriers cited were lack of private space (13%) and taking time off work (9%). No clear preference for phone versus video Telehealth was noted (approximately 40% each), but 7% expressed concern about bi-directional video communication. This may be related to the privacy and security concerns expressed by 20% of respondents. However, only 5% reported using the electronic health record (EHR) based secure communication portal. Conclusion: Sleep care via Telehealth is preferred by most patients during the COVID pandemic and is acceptable to two-thirds of patients for the long-term. In addition to access to personal devices or the internet, privacy concerns were a barrier to Telehealth. We plan to increase patient enrollment in the EHR-based portal to deliver telehealth services and communication securely to mitigate these barriers. Support (if any):